Infrastructure and clinical practice for the detection and management of trauma-associated haemorrhage and coagulopathy. - Driessen, A.; Schäfer, N.; Albrecht, V.; Schenk, M.; Fröhlich, M.; Stürmer, E.; Maegele, M. (European Journal of Trauma & Emergency Surgery, 2015)
Purpose: Early detection and management of post-traumatic haemorrhage and coagulopathy have been associated with improved outcomes, but local infrastructures, logistics and clinical strategies may differ. Methods: To assess local differences in infrastructure, logistics and clinical management of trauma-associated haemorrhage and coagulopathy, we have conducted a web-based survey amongst the delegates to the 15th European Congress of Trauma and Emergency Surgery (ECTES) and the 2nd World Trauma (WT) Congress held in Frankfurt, Germany, 25-27 May 2014. Results: 446/1,540 delegates completed the questionnaire yielding a response rate of 29 %. The majority specified to work as consultants/senior physicians (47.3 %) in general (36.1 %) or trauma/orthopaedic surgery (44.5 %) of level I (70 %) or level II (19 %) trauma centres. Clinical assessment (>80 %) and standard coagulation assays (74.6 %) are the most frequently used strategies for early detection and monitoring of bleeding trauma patients with coagulopathy. Only 30 % of the respondents declared to use extended coagulation assays to better characterise the bleeding and coagulopathy prompted by more individualised treatment concepts. Most trauma centres (69 %) have implemented local protocols based on international and national guidelines using conventional blood products, e.g. packed red blood cell concentrates (93.3 %), fresh frozen plasma concentrates (93.3 %) and platelet concentrates (83 %), and antifibrinolytics (100 %). 89 % considered the continuous intake of anticoagulants including 'new oral anticoagulants' and platelet inhibitors as an increasing threat to bleeding trauma patients. Conclusions: This study confirms differences in infrastructure, logistics and clinical practice for the detection and management of trauma-haemorrhage and trauma-associated coagulopathy amongst international centres. Ongoing work will focus on geographical differences.